Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region - Barker, Gary M. (Zootaxa, 2018)
Athoracophoridae are succineoidean terrestrial slugs that constitute a distinctive faunal element of the South West Pacific biogeographic region, with representatives in New Guinea, Australia, New Caledonia, Vanuatu and New Zealand. Despite many studies on morphology, taxonomy and phylogenetic relationships since the first species description in 1832, the understanding of the diversity within the family, as reported in published literature, remains poor with regional disparities in collection and systematic effort, in taxonomic concepts, and in adherence to type concepts. The systematics of Athoracophoridae needs to be re-evaluated through a modern, phylogenetic approach to properly document infra-familial evolution and taxon diversity, advance understanding of evolutionary relationships with other Eupulmonata, and to delineate evolutionary units for conservation prioritization. A catalogue of all class-, family-, genus- and species-group names erected for or used to include Athoracophoridae over the 185 year period 1832 to 2017 is provided, as a first step towards a systematic revision. The following nomenclatural changes are made: lectotype designation for Aneitea macdonaldii Gray, 1860; lectotype designation for Janella papillata Hutton, 1879; type species designation for Amphikonophora Suter, 1897; and lectotype designation for Athoracophorus verrucosus Simroth, 1889.